The relationship between non-audit service fees and audit fees in the banking sector in Malaysia - Shafie, Rohami; Che Ahmad, Ayoib; Md Ali, Azham (Universiti Utara Malaysia, 2007)
The issue of audit fees and non-audit fees charged by the audit firms has been discussed regularly in accounting and auditing literature. Recently, due to the corporate scandals in United States, the issue is discussed together with a host of revelations about audit failures that led to the companies’ demise. The auditing profession is being badly blamed and some suggest that this could be due to the audit firm’s reliance more on non-audit services rather than the audit itself. Therefore, this study attempts to probe the situation in Malaysia using the banking sector as the subject of interest. Specifically, it tries to examine the impact of non-audit services conducted by audit firms to these banks on audit fees. The results showed that the variable of non-audit fees is statistically significant in determining audit fees as predicted. Further sensitivity analysis showed that the results are robust to different measurements and company size.